Inovasi Dan Kolaborasi: Peran Smes And Start-Up Incubator Project Officer Dalam Peningkatan Daya Saing Bisnis Di Solo Technopark - Rangga Meulligga Daniarko; Nurhadi Nurhadi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Solo Technopark is a strategic technology and business center located in the city of Solo, Central Java, playing a crucial role in driving the development of technology-based businesses in the region. Within it, there is a division that specializes in comprehensive understanding of business needs and the selection of incubation methods suitable for SMEs and startups, known as SSIPO (SMEs and Startup Incubator Project). This research aims to determine the role of SSIPO in enhancing the competitiveness of businesses in Solo Technopark. The study employs a qualitative descriptive method, gathering data through field observations, interviews with relevant sources, and documentation. The researcher utilizes primary data sources from observations and interviews, as well as references from books, journals, and the UPTD Solo Technopark website. Data analysis technique is adapted using descriptive-narrative methods. The research findings reveal that SSIPO's role involves effective collaboration and innovation-based facilitation for SMEs and startups, initiating three programs specifically designed for these entities.